The role of plasticity and hydrogen flux in the fracture of a tempered martensitic steel: A new design of mechanical test until fracture to separate the influence of mobile from deeply trapped hydrogen. (March 2020) - Guedes, D.; Cupertino Malheiros, L.; Oudriss, A.; Cohendoz, S.; Bouhattate, J.; Creus, J.; Thébault, F.; Piette, M.; Feaugas, X.
Abstract: The design of an electrochemical permeation device on a tensile machine has allowed to control the hydrogen flux and to isolate the effects of trapped and mobile hydrogen on the hydrogen embrittlement of a martensitic steel. Based on a local approach of fracture, tensile tests on several notched specimens were completed in order to investigate the impact of hydrostatic stress, equivalent plastic strain, hydrogen concentration and flux on the damage processes. Analysis of the fracture surfaces revealed that trapped hydrogen favors ductile fracture, enhancing nucleation and growth of voids by reducing the interface energy between precipitates/inclusions and matrix. Mobile hydrogen leads to quasi-cleavage along the substructure (lath and/or blocks) boundaries at mainly the 101 planes. For both mechanisms, the mutual interaction between hydrogen and dislocations (drag process increasing hydrogen diffusion and hydrogen favoring dislocations mobility) has a large contribution to the hydrogen embrittlement of the martensitic steel. Graphical abstract: Image, graphical abstract